The Role of Adult Education and English Language Education in Nation-Building: A Case Study of the Emmanuel Bible Institute of Oradea, Romania - Cheri Pierson; Richard A. Orem (Adult Education Research Conference, 1999)
English as a language of theological instruction necessarily includes influential elements of Western Protestant styles of critical thinking. This study focuses on the role and implications of English as a foreign language at the Emmanuel Bible Institute in Oradea, Romania. The influence of English in theological development and subsequent nation building are also addressed